Dossier’s Presentation (second part): Plato’s Phaedo. Platonists Brazilian Society Conference - Xavier, Dennys Garcia (Revista Archai, 2025)
Dossier’s Presentation (second part): Plato’s Phaedo. Platonists Brazilian Society Conference